Sustained Release‐Driven Formation of Ultrastable SEI between Li6PS5Cl and Lithium Anode for Sulfide‐Based Solid‐State Batteries. Issue 4 (18th December 2020) - Chen, Ya; Li, Wenwen; Sun, Changzhi; Jin, Jun; Wang, Qing; Chen, Xiaodong; Zha, Wenping; Wen, Zhaoyin
Abstract: The sulfide‐type solid electrolyte (SSE) is considered a promising candidate for solid‐state lithium metal batteries (SSLMBs) owing to its advantages of superior ionic conductivity. Nevertheless, the incompatibility of the sulfide and lithium metal can result in undesirable interface resistance and rapid Li dendrite growth, which seriously hinders its commercial applications. Herein, inspired by the moderation and long duration of sustained release drug carriers when combined with active pharmaceutical ingredients in the biomedical field, poly (propylene carbonate) (PPC) and lithium bis (trifluoromethanesulfonyl) imide (LiTFSI) gradually interact with a Li anode with constantly decreased Li/SSE interfacial resistance. In addition to intimate contact, the ultrastable LiF‐enriched solid electrolyte interphase (SEI) is in situ formed via a sustained release effect, which suppresses the Li dendrite effectively. As a result, the symmetric cells demonstrate stable cycling performance for 1200 h at a current density of 0.1 mA cm −2 and 300 h at 0.5 mA cm −2 . Moreover, LiFePO4 / Li6 PS5 Cl /Li SSLMB delivers a high discharge capacity of over 132.8 mAh g −1 for 900 cycles at 1C with steady Coulombic efficiency. Therefore, this sustained release mechanism and its initially successful application in interfacial modification increase the potential for commercial applications of SSLMBs. Abstract : A poly (propylene carbonate) (PPC)‐based polymer is employed as an initiator for anodic interface modification in sulfide‐based solid‐state lithium metal batteries. Through gradual degradation of PPC, the solvated LiTFSI is released and reacts with the Li anode in the presence of a polysulfide species, resulting in the in situ formation of ultrastable LiF‐enriched a solid electrolyte interphase at the Li/ Li6 PS5 Cl interface.